Gambaran Tingkat Pengetahuan Perawat Dalam Penerapan Bundle Vap (Ventilator Associated Pneumonia) Di Ruang Icu - Nababan, Sortha Martha Nurhayati; Angelina, Ria; Natalia, Lidya (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
Abstract Ventilator-Associated Pneumonia (VAP) is a serious complication in patients undergoing mechanical ventilation in intensive care units (ICUs). Preventing VAP is crucial, and nurses' knowledge of the VAP Bundle (a series of preventive practices) plays a pivotal role in these efforts. This research employs a quantitative descriptive design and utilizes a validated knowledge questionnaire. The study findings reveal that the majority of nurses have good knowledge (60.75%) about the VAP Bundle (Category C1 Knowledge). In the Comprehension category (C2), 48.10% of nurses demonstrate a good understanding. Meanwhile, in the Application category (C3), 74.69% of nurses effectively apply VAP Bundle practices. Adequate nurse knowledge regarding the VAP Bundle serves as a critical foundation for preventing VAP in the ICU. These results can be used as a basis for further training and educational program development, aiming to enhance patient safety by effectively preventing VAP.